A lamb to the slaughter [large type] - Johnstone, William W.; Johnstone, J. A. (Tinhorn Western, 2024)
"Tinhorn, Texas, is a small town, quiet and peaceful. Sheriff Buck Jackson and Deputy Flint Moran go to great pains to keep it that way. So when two drifters arrive in town--one nursing a bullet wound--the lawmen suspect trouble ain't far behind. Bart McCoy and Roy Tate claim to be cattlemen and have more than enough cash to prove it. But Buck and Flint don't believe Tate's story of accidentally shooting McCoy while cleaning his gun. Then four more men arrive, armed to the teeth, looking to fill the supposed ranchers full of lead. Turns out six outlaws robbed a Wells Fargo Office and murdered a guard. Then the thieves turned against each other--and McCoy and Tate's escaped with the loot. Now their former friends have hunted them to Tinhorn and will massacre everyone in town to retrieve their ill-gotten gains. Buck and Flint have sworn to protect Tinhorn to the fullest extent of the law. And in the wild west of Texas, the only law bandits and killers understand comes from the business end of a gun.